(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we present a numerical solution for an open-loop Nash differential game modeling competition between two firms. Using the fourth-order Runge-Kutta method, we computed the numerical solution and analyzed the stability of the open-loop Nash equilibrium. Additionally, we examined the uniform convergence of the solution. Finally, an illustrative example is presented to clarify the results, accompanied by figures to illustrate the findings.